How to improve the identification of patients with cancer eligible for genetic counselling?. (8th June 2020) - Bracci, Raffaella; Gasperini, Beatrice; Capalbo, Maria; Campanelli, Tamara; Caimmi, Eleonora; Mattioli, Rodolfo; Espinosa, Emma; Prospero, Emilia
Abstract: Objective: International guidelines recommend genetic counselling and if indicated the genetic testing for treatment, disease prevention and follow‐up for patients and their relatives. However, there is limited utilisation of genetic counselling. This study aimed to verify whether an individual semi‐structured guideline‐based interview improves the identification of patients eligible for genetic counselling. Methods: Unselected patients with cancer were interviewed. A dedicated nurse provided an ad‐hoc guideline‐based questionnaire to assess the presence of criteria for a possible hereditary breast and ovarian cancer syndrome or hereditary non‐polyposis colorectal cancer syndrome (Lynch syndrome). The interest of patients to undergo genetic counselling was also investigated. Results: Ninety patients were enrolled in the study; 20 (22.2%) of these had already undergone genetic counselling. The interview identified 23 (32.8%) of the remaining 70 patients that were eligible for genetic counselling. Two‐third of the patients ( n = 59) were interested in genetic counselling irrespective of socio‐demographic factors or cancer type. A logistic regression analysis for age, gender, parental status, educational level and cancer type did not reveal any independent factor that was associated with patients who had previous genetic counselling. Conclusions: Our preliminary findings suggest that a semi‐structured guideline‐based interview can substantially improve the identification of patients eligible for genetic counselling.